Effect of Diabetes Mellitus on Central Corneal Thickness ? A Comparative Study - Islam, Qamar-ul- (Pakistan Journal of Ophthalmology, 2017)
Purpose: To compare central corneal thickness (CCT) of diabetes Mellitus (DM) patientswith age matched subjects without DM and to evaluate the correlation of CCT with glycemic status, duration of DM and severity of diabetic retinopathy (DR). Study Design: Cross sectional comparative study. Place and duration of study: Eye Department, PNS Shifa Karachi from March 2016 to February 2017. Material and Methods: Patients with ages between 20 to 80 years of either gender who were diagnosed to have DM were recruited in the study. Control group comprised of age matched healthy volunteers who did not have DM. CCT was evaluated in each subject with non-contact specular microscope (SP-3000 P, Topcon Corporation, Japan) and all the findings were endorsed on a pre designed performa. SPSS version 13.0 was used for analysis of data. Result: Two hundred and fifty two eyes (126 diabetic patients and 126 healthy controls) were evaluated. Both groups were age and gender matched (p > 0.05). Mean CCT of diabetic population was 512.21 ± 32.68 µm while mean CCT of control group was 498.83 ± 28.98 µm (p = 0.001). Difference in CCT values between subgroups of patients with no DR, with NPDR and PDR was statistically non-significant (p = 0.810). Pearson’s correlation analysis showed that duration of DM (r = 0.022, p = 0.809), HbA1c (r = 0.103, p = 0.251), and severity of DR (r = 0.022, p = 0.805) did not show any significant correlation with CCT. Conclusion: Significantly thicker CCT was found in patients with DM as compared to healthy age matched controls.